Plant-endophyte mediated improvement in physiological and bio-protective abilities of marigold (Tagetes patula) - Naveed, Muhammad; Hafeez, Sidra; Rafique, Munazza; Mumtaz, Muhammad Zahid; Subhani, Zinayyera; Holatko, Jiri; Hammerschmiedt, Tereza; Malicek, Ondrej; Mustafa, Adnan; Kintl, Antonin; Brtnicky, Martin (Frontiers in Plant Science, 2022)
Endophytic bacteria improve the growth, physiology, and metabolite profile of plants. They are known as potential biocontrol agents of soil-borne diseases. This study evaluated the effects of endophytic bacterial strains on growth, vase life, biochemical attributes, and antioxidant and nematicidal activities of French marigold (Tagetes patula). French marigold seeds were sole and consortium inoculated with three promising endophytic bacterial strains, Burkholderia phytofirmans (PsJN), Enterobacter sp. (MN17), and Bacillus sp. (MN54). The vase life of French marigold was promoted by 66.6% in the individual application of PsJN and 100% in plants treated with consortium compared to the uninoculated control. The shoot and root fresh weights were also increased by 65.9 and 68.7%, with the combined application of all three strains. The total phenolics, flavonoid, and protein contents were higher in consortium treatment with an increase of up to 38.0, 55.9, and 65.9%, respectively, compared to the uninoculated control. Furthermore, combined application of endophytic bacterial strains promoted DPPH radical scavenging, mortality of plant-parasitic nematodes, and ferric reducing antioxidant power activities with increase of up to 278.0, 103.8, and 178.0%, respectively, compared to uninoculated control. An increase in antioxidant activities of ascorbate peroxidase (APX), catalase (CAT), glutathione peroxidase (GPX), and superoxide dismutase (SOD) were observed up to 77.3, 86.0, 91.6, and 102.9%, respectively by combined application of endophytic bacterial strains. So, given the economic importance of floriculture crops, endophytic bacterial isolates studied here have shown a great potential for improving the productivity of cultivated ornamental French marigold.